2008
DOI: 10.1177/1753465808088903
|View full text |Cite
|
Sign up to set email alerts
|

Review: Surfactant protein D: A lung specific biomarker in COPD?

Abstract: A major impediment in the development of novel drugs for chronic obstructive pulmonary disease (COPD) has been the scarcity of a well-validated, robust, and easily obtainable intermediate end point such as serum biomarkers. To date the best serum biomarkers in COPD have been non-speci"c pro-in"ammatory molecules synthesized largely by extra-pulmonary organs. In COPD, an ideal biomarker would be one that (1) was produced mostly in the lungs (and was reliably measurable in the peripheral circulation using commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 77 publications
0
41
0
2
Order By: Relevance
“…Bowler 36 stated that clinical research in COPD has been hampered by the lack of validated blood biomarkers and discussed the evidence supporting SPD as a COPD biomarker. Sin et al 37 commented that the scarcity of a well-validated, robust, and easily obtainable intermediate end point such as serum biomarkers is a major impediment in the development of novel drugs for COPD and reported SPD as a promising systemic biomarker fulfilling some of the criteria of a biomarker. Dickens et al 26 (ECLIPSE study investigators) also expressed the need for biomarkers to better characterize individuals with COPD and to aid in the development of therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Bowler 36 stated that clinical research in COPD has been hampered by the lack of validated blood biomarkers and discussed the evidence supporting SPD as a COPD biomarker. Sin et al 37 commented that the scarcity of a well-validated, robust, and easily obtainable intermediate end point such as serum biomarkers is a major impediment in the development of novel drugs for COPD and reported SPD as a promising systemic biomarker fulfilling some of the criteria of a biomarker. Dickens et al 26 (ECLIPSE study investigators) also expressed the need for biomarkers to better characterize individuals with COPD and to aid in the development of therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we cannot exclude the possibility that SP-D upregulation at the gene expression level in hyperglycemic GDM women observed in our research could be an effective compensation for enhanced oxidative stress and inflammation, the two interconnected processes induced by high glucose concentration, in diabetic patients, since SP-D has been recognized as a molecule with antioxidant and anti-inflammatory properties. 16,17 We also observed the existence of clinical associations between leukocyte SFTPD expression and fasting glycemia, insulin resistance, and inflammation among pregnant women, which reflect functional and biological importance of this biomolecule during gestation. The reasons for these associations are currently unknown.…”
mentioning
confidence: 91%
“…15 Moreover, SP-D exhibits anti-inflammatory and antioxidant properties through a decrease of the expression of some pro-inflammatory cytokines and a reduction of lipid peroxidation, respectively. 16,17 More recently, SP-D has emerged as a factor that appears to link to metabolic disorders. In fact, decreased serum SP-D concentration has been reported in subjects with obesity and T2DM and it negatively correlates with fasting and post-load serum glucose.…”
Section: Introductionmentioning
confidence: 99%
“…29,40 Recent studies have shown the importance of S-PD in antibacterial defense against pathogenic species encountered in bronchial colonization in COPD and in exacerbations: Pseudomonas aeruginosa, Klebsiella pneumoniae, Haemophilus influenzae, Streptococcus pneumoniae or Staphylococcus aureus. 40 S-PD is elevated in COPD and in smokers, and is associated with an increased risk of exacerbations. Inhaled or systemic corticosteroids lower the S-PD.…”
Section: Surfactant Protein D (S-pd)mentioning
confidence: 99%
“…39,40 S-PD modulates the immune response (decreases the expression of pro-inflammatory cytokines, decreases lymphocytes and oxidative stress and increases phagocytosis). 29,40 Recent studies have shown the importance of S-PD in antibacterial defense against pathogenic species encountered in bronchial colonization in COPD and in exacerbations: Pseudomonas aeruginosa, Klebsiella pneumoniae, Haemophilus influenzae, Streptococcus pneumoniae or Staphylococcus aureus. 40 S-PD is elevated in COPD and in smokers, and is associated with an increased risk of exacerbations.…”
Section: Surfactant Protein D (S-pd)mentioning
confidence: 99%